Economic growth rates of legumes with low water consumption - Herrera Flores, Teresa Susana; Moreno Contreras, María Guadalupe; Licea de Anda, Eva Marcela; Arratia Castro, Alda Alejandra (Revista Mexicana de Ciencias Agrícolas, 2019)
The objective of this work was to analyze the production behavior and economic growth rates of beans (Phaseolus vulgaris L.) and chickpea (Cicer arietinum L.). In Mexico, about 1.93 million hectares are destined to the cultivation of five legumes, which corresponds to beans (91.7%), chickpeas (6.4%), faba beans (1.4%), lentils (0.4%) and peas (0.1%). The production data were obtained from the statistical yearbook of production (http://infosiap.siap.gob.mx/aagricola-siap-gb/icultivo/, for the period 2013-2017). The area planted with beans, presented a positive annual growth rate of 0.84%, with the state of Zacatecas and Durango participating with 59% of the total ha nationwide, while Guanajuato has a 6% share, with Penjamo being the which has a total of 8% of the surface in the state. In chickpea, an annual average growth rate was obtained, with negative values, for the planted area, -5.01%, being Sinaloa and Sonora those that represent 77% of the total area sown nationally, Guanajuato contributes 6%, while that the municipalities of Pénjamo and Valley of Santiago had the highest values. The price per ton and the value of the production had positive values with respect to the average annual growth rates in the bean crop, while in chickpeas the growth rates with positive values were the yield, the price per ton and the production value.
Keywords: Cicer arietinum L; Phaseolus vulgaris L.; bean; chickpea; production